Review of Methods to Reduce Energy Consumption in A Smart City Based On IoT and 5G Technology - Sánchez-Cano, Julieta Evangelina; Garcia-Quilachamin, Washington Xavier; Pérez-Véliz, Jonny; Herrera-Tapia, Jorge; Atiencia-Fuentes, Kelvin (International Journal of Online and Biomedical Engineering (iJOE), 2021)
The evolution of the technology 5G has influenced the Internet of the Things (IoT) according to the wireless communications of minor latency, and major speed compared to the existing technologies. Consequently, from the 21st century, 5G will act as the spinal column of the IoT and will level the way for the design and deployment of a Smart City, nevertheless, this progress has a negative point which is demonstrated in the energy consumption. The target of this investigation is to announce methods to reduce the consumption of energy in one Smart City based on the IoT and the technology 5G. The results obtained in this investigation allow determining that 5G and the IoT will have a major energy consumption with about 80 % of the entire potency, due to the transmission and reception of a big quantity of information in a Smart City. Likewise, this research, contributes to the knowledge, presenting a review of methods that allow minimizing energy consumption and projects that improve energy efficiency.